Viral Vectors for Plant Genome Engineering - Zaidi, Syed Shan-e-Ali; Mansoor, Shahid (Frontiers in Plant Science, 2017)
Recent advances in genome engineering (GE) has made it possible to precisely alter DNA sequences in plant cells, providing specifically engineered plants with traits of interest. Gene targeting efficiency depends on the delivery-method of both sequence-specific nucleases and repair templates, to plant cells. Typically, this is achieved using Agrobacterium mediated transformation or particle bombardment, both of which transform only a subset of cells in treated tissues. The alternate in planta approaches, stably integrating nuclease-encoding cassettes and repair templates into the plant genome, are time consuming, expensive and require extra regulations. More efficient GE reagents delivery methods are clearly needed if GE is to become routine, especially in economically important crops that are difficult to transform. Recently, autonomously replicating virus-based vectors have been demonstrated as efficient means of delivering GE reagents in plants. Both DNA viruses (Bean yellow dwarf virus, Wheat dwarf virus and Cabbage leaf curl virus) and RNA virus (Tobacco rattle virus) have demonstrated efficient gene targeting frequencies in model plants (Nicotiana benthamiana) and crops (potato, tomato, rice, and wheat). Here we discuss the recent advances using viral vectors for plant genome engineering, the current limitations and future directions.